If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 72 = -3(x + 4) + -21x Reorder the terms: 72 = -3(4 + x) + -21x 72 = (4 * -3 + x * -3) + -21x 72 = (-12 + -3x) + -21x Combine like terms: -3x + -21x = -24x 72 = -12 + -24x Solving 72 = -12 + -24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24x' to each side of the equation. 72 + 24x = -12 + -24x + 24x Combine like terms: -24x + 24x = 0 72 + 24x = -12 + 0 72 + 24x = -12 Add '-72' to each side of the equation. 72 + -72 + 24x = -12 + -72 Combine like terms: 72 + -72 = 0 0 + 24x = -12 + -72 24x = -12 + -72 Combine like terms: -12 + -72 = -84 24x = -84 Divide each side by '24'. x = -3.5 Simplifying x = -3.5
| K-7=10 | | 3+z=18 | | 1.5r=8 | | -5x=18-3x | | 0.8m=80 | | -6+4y=-12 | | 5x-4(x-6)=1 | | h=-16t^2+150t+1 | | 2x+y=10-3x | | 2x^2-15x+15=8-x^2-5x | | (u+3)2=2u+11u+15 | | X^4-7x+3=0 | | 2x^4-7x+3=0 | | 2x+3x-15=25 | | -2+x-4x=11 | | 5(6)+3(7)= | | -4+3x=-12+25xfraction | | 2y-4*0=10 | | x-2 = 9 (4-10x)4 | | 9y-5y-9=48.80 | | W-8=23 | | 2y+-4*-2=10 | | -42=-6(z-3) | | 5x+9=82-8x | | -3k^2g-[4kg^2-(6k^2g-2kg^2)]=0 | | 3x-3y+3=2 | | Log(3t+1)=5 | | 49=17(t+1) | | 14abc-[3ab^2c+(4a^2bc)-(-3ab^2c-5abc+5a^2bc)]=0 | | -3y+3=2 | | 3.8=m+9.7 | | -3y+3=0 |